Is Israel Its Brother's Keeper? Responsibility and Solidarity in the Israeli–Palestinian Conflict. (5th April 2017) - Lederman, Zohar; Shepp, Emily; Lederman, Shmuel
Abstract: This article examines the Israeli government's role in supporting living conditions conducive to health in the occupied Palestinian territories (OPT). Limiting the discussion to public health, the authors argue that—whether justified in its overall political policy—the Israeli government and people are legally and ethically obligated to care for the well-being of the Palestinian people. The authors first review the current situation in the OPT and compare health statistics with Israel. Next, the authors make three arguments as to why the Israeli government and citizens should assist the Palestinian people: moral responsibility, legal responsibility and solidarity. Based on these, the authors make the case for Israel's moral duty to ensure that Palestinian people living in the OPT achieve equitable levels of health as compared to Israeli citizens, while minimizing restrictions on Palestinian self-determination. The authors urge the Israeli government and citizens to improve Palestinian's daily living conditions, tackle inequitable distribution of power and allow international support in these efforts. Hospital Admission must therefore be open to every patient that needs it, irrespective of whether he has money or not, whether he be Jew or heathen. (Virchow, 1879 : 26)